Treatment of Inflammatory Bowel Disease: A Comprehensive Review - Cai, Zhaobei; Wang, Shu; Li, Jiannan (Frontiers in Medicine, 2021)
Inflammatory bowel disease (IBD), as a global disease, has attracted much research interest. Constant research has led to a better understanding of the disease condition and further promoted its management. We here reviewed the conventional and the novel drugs and therapies, as well as the potential ones, which have shown promise in preclinical studies and are likely to be effective future therapies. The conventional treatments aim at controlling symptoms through pharmacotherapy, including aminosalicylates, corticosteroids, immunomodulators, and biologics, with other general measures and/or surgical resection if necessary. However, a considerable fraction of patients do not respond to available treatments or lose response, which calls for new therapeutic strategies. Diverse therapeutic options are emerging, involving small molecules, apheresis therapy, improved intestinal microecology, cell therapy, and exosome therapy. In addition, patient education partly upgrades the efficacy of IBD treatment. Recent advances in the management of IBD have led to a paradigm shift in the treatment goals, from targeting symptom-free daily life to shooting for mucosal healing. In this review, the latest progress in IBD treatment is summarized to understand the advantages, pitfalls, and research prospects of different drugs and therapies and to provide a basis for the clinical decision and further research of IBD.